Peningkatan Ketahanan Keluarga di Masa Pandemi Melalui Kegiatan Home Visit - Nefi Darmayanti; Astrie Anggraini; Diajeng Tri Utami; Dini Fatmahsari Batubara; Juhro Ulya Wardani Ritonga; Nazwa Elyana (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2023)
Large-Scale Social Restrictions to control the transmission of Covid-19 have paralyzed the economy. The impact is a decrease in economic income which affects the family's ability to survive during the Covid-19 pandemic. This study aims to determine the economic resilience of families on the coast of Bagan Kuala village during the Covid-19 pandemic. Qualitative method of literature study where the method used is to prepare activities that must be carried out with the method of collecting library data, reading and taking notes and recording research materials. The results show how the impact of the pandemic on the economic resilience of coastal families in Bagan Kuala village during the Covid-19 pandemic has decreased, especially in terms of income and ability to meet family needs. However, from the aspect of housing ownership, financing for children's education, and family financial security, the economic resilience of families on the coast of Bagan Kuala village can be considered quite good. This study recommends the need for a fairly good family financial management strategy. Pembatasan Sosial Berskala Besar untuk mengendalikan penularan Covid-19 telah melumpuhkan perekonomian. Dampaknya adalah penurunan penghasilan yang berimbas pada kemampuan ekonomi keluarga bertahan selama pandemi Covid-19. Penelitian ini bertujuan untuk mengetahui ketahanan ekonomi keluarga di pesisir pantai desa Bagan Kuala pada masa pandemi Covid-19. Metode kualitatif studi literatur dimana metode yang digunakan adalah serangkaian kegiatan yang berkenanaan dengan metode pengumpulan data pustaka, membaca dan mencatat serta mengolah bahan penelitian. Hasil penelitian menunjukkan bagaimanadampak pandemi terhadap ketahanan ekonomi keluarga pesisir pantai desa Bagan Kuala pada masa pandemi Covid-19 mengalami penurunan khususnya dari sisi pendapatan dan kemampuan memenuhi kebutuhan keluarga. Namun dari aspek kepemilikan tempat tinggal, pembiayaan pendidikan anak, dan jaminan keuangan keluarga, ketahanan ekonomi keluarga di pesisir pantai desa Bagan Kuala dapat dinilai cukup baik. Penelitian ini merekomendasikan perlunya strategi pengelolaan keuangan keluarga yang cukup baik.